Antibacterial activity of the bioactive compounds identified in three woody plants against some pathogenic bacteria. (August 2018) - Ashmawy, Nader A.; Salem, Mohamed Z.M.; EL-Hefny, Mervat; Abd El-Kareem, Mamoun S.M.; El-Shanhorey, Nader A.; Mohamed, Abeer A.; Salem, Abdelfattah Z.M.
Abstract: Three bacterial isolates were identified from infected potato tubers showing soft and blackleg like symptoms as well as one isolate from infected pear tree showing crown gall symptom. Conventional and molecular identification proved that bacterial isolates belonging to Pectobacterium carotovorum subsp. carotovorum, Pectobacterium atrosepticum, Dickeya solani and Agrobacterium tumefaciens . The above plant bacterial isolates and human pathogenic bacteria Escherichia coli, Sarcina lutea, and Staphylococcus aureus were used for the bioassay. The chloroform leaf extracts from Duranta plumieri variegata, Lantana camara, and Citharexylum spinosum were assayed for their antibacterial activity by measuring the inhibition zones and minimum inhibitory concentrations (MICs). The suggested chemical compositions of extracts were analyzed using GC/MS apparatus. The main compounds in leaf extract of L. camara were 5, 8-diethyl-dodecane, pyrimidin-2-one, 4-[ N -methylureido]-1-[4-methylaminocarbonyloxymethyl, oleic acid, 3-(octadecyloxy)propyl ester; in D. plumieri were 4, 7-dimethoxy-2-methylindan-1-one and 5-(hexadecyloxy)-2-pentadecyl-, trans-1, 3-dioxane; and in C. spinosum were N -[5-(3-hydroxy-2-methylpropenyl)-1, 3, 4, 5-tetrahydrobenzo[cd]indol-3-yl]- N -methylacetamide. Promising activity was found against A. tumefaciens, E. coli, P. carotovorum, Sar. lutea, and Staph. aureus with MIC values of 8, 128, 64, 500 and 500 μg/mL, respectively, as L. camara leaf extract was applied. D. plumieri leaf extract showed good activity against D. solani and P. atrosepticum with MIC values of 16 μg/mL and 128 μg/mL, respectively. On the other hand, weak bioactivity was found with leaf extract from C. spinosum . It could be concluded that leaf extracts from D. plumieri and L. camara have a promising antibacterial agents. Graphical abstract: Image 1 Highlights: Leaf extracts from three woody plants belong to Verbenaceae were evaluated. Phytopathogenic bacteria were isolated and identified from diseased tissues. Standard human pathogenic bacteria were used. Duranta plumieri, and Lantana camara extracts showed good activity. Promising activity was found against A. tumefaciens, as L. camara leaf extract used.